Media for Teaching English to Children with Mental Retardation - Ramadanti, Aulia (Universitas Nahdatul Ulama Surabaya, 2022)
Teaching English for children with mental retardation of course is a challenging experience. Even for the professional teacher, it is a challenge to teach English for children with mental retardation. This become an issue that teacher must provide good explanation especially the media. Media is considered as an important thing when teacher teach. The writer noticed this when I had an observation in SLB (School for Children with Special Need) Aisyiyah Tulangan. The observation conducted on 17, 18, 24 November and 1 & 2 December 2021. Observations were carried out in the special SMPLB class for mentally retarded children. SLB Aisyiyah Tulangan still lacks of media for learning, especially for English. As previously stated, English is a local content which is not taught in schools every day. The school also does not have a special module for learning English. English is only taught when the teacher wants to teach English, the rest of the teachers are free to provide any material for students. The module for students is only limited to practice questions that are made independently by the teacher according to the existing curriculum, there are no supporting books such as textbooks for students. This is the weakness for this school, the lack of support from the school foundation to support learning in schools, even though the teachers have given their best for the students.